2005
DOI: 10.1614/wt-04-130r.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions ofPyricularia setariaewith Herbicides for Control of Green Foxtail (Setaria viridis)

Abstract: Sethoxydim, tralkoxydim, imazethapyr, quinclorac, propanil, glyphosate, and glufosinate were tested at rates below those recommended by the manufacturers withPyricularia setariaeNiskada under greenhouse conditions for control of green foxtail. At one-tenth of the recommended rate in a 100 L/ha carrier volume, only the sethoxydim–P. setariaecombination achieved more effective green foxtail control when compared with the herbicide or pathogen alone. Selected herbicides at one-tenth, one-fourth, and one-half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…The authors demonstrated that an application of glyphosate prior to Myrothecium verrucaria provided better weed control in kudzu (Pueraria lobata), redvine (Brunnichia ovata), and trumpetcreeper (Campis radicans). This was also the case for green foxtail, which was sufficiently controlled when treated with glyphosate prior to Pyricularia setariae inoculation (Peng & Byer, 2005). These results suggest that timing of glyphosate application in relation to combined treatment with a bioherbicide is important.…”
Section: Leaf Pathogenssupporting
confidence: 53%
See 1 more Smart Citation
“…The authors demonstrated that an application of glyphosate prior to Myrothecium verrucaria provided better weed control in kudzu (Pueraria lobata), redvine (Brunnichia ovata), and trumpetcreeper (Campis radicans). This was also the case for green foxtail, which was sufficiently controlled when treated with glyphosate prior to Pyricularia setariae inoculation (Peng & Byer, 2005). These results suggest that timing of glyphosate application in relation to combined treatment with a bioherbicide is important.…”
Section: Leaf Pathogenssupporting
confidence: 53%
“…Wyss et al (2004) reported that certain pesticides and their adjuvants affected spore germination and growth of Phomopsis amaranthicola, an effective bioherbicides against Amaranthus species. Several herbicides such as glyphosate had also negative effects on spore germination of P. setariae (Peng & Byer, 2005). Thus, one strategy to overcome direct toxic effects of herbicides is a sequential rather than simultaneous application of the synthetic herbicide and the bioherbicides.…”
Section: Leaf Pathogensmentioning
confidence: 99%
“…Recently, several herbicides, including glyphosate, were tested at reduced rates for possible interactions with the fungal pathogen, Pyriculoria setariae Niskoda, for the control of green foxtail ( Setoria viridis [L.] Beauv.) (Peng & Byer 2005). Propanil ( N‐ [3,4‐dichlorophenyl] propanamide), quinclorac (3,7‐dichloro‐8‐quinolinecarboxylic acid), and sethoxydim {2‐(1‐[ethoxyimino]butyl)‐5‐(2‐[ethylthio]propyl)‐3‐hydroxy‐2‐cyclohexen‐1‐one} applied 6 h prior to the pathogen generally resulted in greater efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, a host-specific fungal pathogen, Pyricularia setariae Nisikado, was efficacious against GFT seedlings, including the resistant biotype 7 . Applying sethoxydim at sub-lethal doses prior to or with P. setariae substantially improved its efficacy against GFT, extending the efficacy to older GFT plants and additional weedy foxtail species 8 . However, the key connections between the physiological and pathological events in this synergistic interaction were not understood.…”
Section: Introductionmentioning
confidence: 99%